Adaptation of Internet of Things Technology to Measure Energy Consumption Levels to Reduce Ergonomics-Based Work Accidents - Berlianty, Intan; Soejanto, Irwan; Titisariwati, Indun; Nursubiyantoro, Eko; Arifin, Miftahol (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
This research focuses on applying Internet of Things (IoT) technology to measure energy consumption levels to reduce work accidents based on ergonomics. Work accidents caused by ergonomic factors, such as physical fatigue and discomfort, can be overcome by understanding and managing energy consumption in the work environment. Comparisons made between IoT-based approaches and traditional methods, such as manual observation and periodic evaluation, are often less efficient and unresponsive to changes in the dynamic work environment.The research methodology consists of three main stages. First, design and implement an IoT system involving intelligent sensors to measure energy consumption and ergonomic factors. Second, real-time data collection by analyzing data using artificial intelligence algorithms. Third, performance comparison between IoT-based and traditional methods through field trials and statistical analysis. The research results are expected to provide new insights regarding the effectiveness and efficiency of IoT technology in managing the risk of work accidents based on ergonomics. Future implications of this research include the potential for widespread use of IoT technology in various industrial sectors to improve worker safety and well-being. In addition, this research can pave the way for developing more sophisticated technological solutions tailored to the specific needs of each sector.